Quem tem voz no Supremo? Uma análise das audiências públicas no processo decisório do STF - Falavinha, Diego Hermínio Stefanutto (2020)
The central question of this research is to verify how public hearings work in the decision-making process of the Supreme Federal Court, so as to map which voices are heard and which interests they represent. This work also aims to analyze whether public hearings can be considered a space capable of adding democratic legitimacy to the STF decisions, if they are a way of technically assisting Ministers in matters unrelated to the legal debate or if they are mere procedural formalism without much influence on the Court's decisions. To do so, this research was developed using a quantitative approach through the systematization and codification of documents referring to the 26 public hearings that took place between 2007 and 25 June 2019. The research showed that public hearings are an instrument of individual action used by the Ministers with broad discretion to decide their agenda and procedure. Its format lacks transparency, which makes it difficult to understand the reasons for choosing the participants. Thus, in spite of the Ministers indicating in the dispatches and in the opening speeches of the hearings that they seek to add democratic legitimacy to their audience, non-legal subsidies for their votes and promoting an interinstitutional dialogue, it was necessary to analyze who were the participants and exhibitors who have access to the STF. Participants who were accepted or who were summoned to the hearings are evenly divided amongst representatives of society's interests, experts,political institutions and justice institutions. However, the analysis of the professional profile of the exhibitors revealed that most of the voices that access public hearings are legal professionals, professors / researchers and public agents, many of them making speeches with technical-scientific content. With this information, we sought to understand how Ministers use the contributions of participants and exhibitors in their votes. As a result, 15 case judgments from public hearings were analyzed, establishing whether the Ministers participated in the sessions and if they used the contributions in their votes, showing that the Ministers use little information in their votes and, with the exception of the Minister who called the hearing, the others do not usually participate in the hearings. Therefore, it was asked why Ministers convene public hearings, concluding that they use them as a form of political promotion of the Supreme Court seeking to add credibility to the institution that appears to be open to the participation of society to discuss causes that are considered to have great public relevance. Finally, public hearings have a democratizing potential by allowing access to various voices in the Court. Nonetheless, its plastered and largely discretionary procedure indicates that the voices most present are those of the Ministers themselves, who have full control of the institute, followed by the professionals who are most present as exhibitors (lawyers, professors / researchers and public agents).